Advanced electric drive vehicles - Emadi, Ali (Energy, power electronics, and machines, 2015)
Preface Electrification is an evolving paradigm shift in the transportation industry toward more efficient, higher performance, safer, smarter, and more reliable vehicles. There is in fact a clear trend to shift from internal combustion engines (ICEs) to more integrated electrified powertrains. Non-propulsion loads, such as power steering and air-conditioning systems, are also being electrified